Interpreting ricardo - Peach, Terry (Cambridge, 1993)
David Ricardo was the leading political economist of the early nineteenth century. This book presents a reconstruction of the substance and evolution of Ricardo's thought on the interrelated topics of value, distribution and accumulation. It also provides a detailed summary of, and critical commentary on, the vast secondary literature. The author rejects Sraffa's influential 'corn model' interpretation of Ricardo's early writings; the alleged similarity between the work of Ricardo and Sraffa; the Hollander and Hicks view of Ricardo's treatment of wages; and the neoclassical interpretation of Marshall and others. He also addresses the role of Ricardo's labour theory of value in his analysis, and Marx's interpretation of it. Dr Peach argues that Ricardo's work has been persistently, and sometimes wilfully, misinterpreted, and that this can be remedied only through an attempt to understand Ricardo's writings in his terms, taking account of his objectives.
Keywords: Economics